Do Managers Value Stock Options and Restricted Stock Consistent with Economic Theory?* - Hodge, Frank D.; Rajgopal, Shiva; Shevlin, Terry (Contemporary Accounting Research, 2009)
We conduct a field survey to investigate whether current mid-level and future entry-level managers (collectively managers) subjectively value stock options and restricted stock consistent with economic theory. We find that managers, on average, subjectively value stock options at greater than their Black-Scholes value and greater than fair-value equivalent restricted stock. This result contrasts with conventional economic wisdom that risk-averse employees discount the Black-Scholes value of an option. With respect to stock options, our results also reveal that managers, on average, have a lottery ticket mentality when subjectively valuing options, they value shorter vesting periods, and they value longer terms to maturity. With respect to stock options and restricted stock, we find that managers tend to extrapolate recently rising stock price trends to arrive at their subjective values. Overall, our results suggest that in some cases standard economic theory does not accurately reflect how managers appear to subjectively value stock options and restricted stock.